(untitled) (World Bulletin of Social Sciences, 2025)
This article analyzes the processes of modernizing the transport and communication systems in the southern regions of Uzbekistan. It provides a detailed discussion of the installation of modern digital automatic telephone exchange (ATS) equipment in the Kashkadarya and Surkhandarya regions, issues related to power supply interruptions, regulation of urban and intercity passenger transport systems, construction of highways and internationally significant road interchanges, electrification of railways, and the modernization of Termez Airport. The article also highlights the outcomes of government programs, foreign investments, and the introduction of modern technologies in the transport and communications sectors.